Evaluation of Interleukin 6 and high sensitive C-reactive protein in relation with Body Mass Index - Elia, Zaid Nabeel; Mustafa, Nisreen Waleed (Diyala Journal of Medicine, 2018)
Background:Obesity is one of the largest public health problem worldwide. It is a multi-factorial chronic disease that increases mortality and the prevalence of heart-related diseases. Adipose tissue secretes large numbers of peptides that resemble cytokines. Interleukin 6 )IL-6( is one of those peptides that are released by adipose tissue. One of the major function of IL-6 is sending signal to liver to secrete C-reactive protein (CRP). Objective:To study the relationship between obesity and inflammation by: estimation of high sensitive C-reactive protein (hsCRP) and IL-6 concentrations in participants sera in relation with different body mass indices (BMI). Patients and Methods: This cross-sectional study was performed through the period of 3 months and 90 participants with the average range of age 25-40 years old were included, they were categorized into three groups ( 30 with BMI less than 25, 30 with BMI ranged between 25-29.9 and 30 with BMI more than 30). Results:The concentrations mean of hsCRP was significantly elevated among the three studied groups as a result of BMI increasing (0.945 mg/L, 1.694mg/L and 2.521mg/L respectively). There was a significant increasing in the mean of IL-6 in relation with increased BMI in all included groups (1.084mg/L, 1.802mg/L and 3.531 mg/L respectively). Linear correlation between the concentrations means of hsCRP and IL-6 were found in all studied groups. Conclusion:This study demonstrated a significant relationship between obesity and inflammatory marker (IL6 and hsCRP) .